ENHANCING MALAYSIA’S WATER LITERACY AGENDA THROUGH DIGITAL GAMIFICATION: A CONCEPTUAL FRAMEWORK FOR SECONDARY EDUCATION - Anggang, Aaron Ismanto; Jafar, Adi; Singh, Soon Singh Bikar (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Water is a critical resource for human well-being and socio-economic development, particularly in rapidly developing countries such as Malaysia, where domestic and industrial water demand continues to increase. Despite receiving high annual rainfall, persistent issues related to excessive consumption, water wastage, pollution, and limited public awareness indicate weaknesses in sustainable water management practices. These conditions reflect an unsatisfactory level of water literacy, especially among young people who will become future water users and decision-makers. Existing teacher-centred instructional approaches have demonstrated limitations in addressing abstract and systems-based water concepts, often resulting in fragmented conceptual understanding and weak attitudinal orientation toward sustainable water use. Interactive digital gamification is positioned as an experiential and learner-centred pedagogical approach that supports deeper cognitive engagement with water-related concepts. This paper presents the conceptual design and instructional framework of an interactive digital gamification module, Water Warriors: Save the World, developed to enhance water literacy among Malaysian secondary school students. The framework integrates game-based mechanics, classroom-oriented learning design, and experiential elements to strengthen students’ water-related knowledge and attitudes toward sustainable water use. The paper further discusses the projected educational outcomes, implementation challenges, and theoretical as well as practical implications of integrating digital gamification into water education to support the development of environmentally responsible future citizens.